Permanent Education: New skills and competences for a sustainable employability in the current socioeconomic and labor context - Pedraza López, Bonifacio (2023)
In the current economic and social context, involved in an intense process of transition (climate change, energy and environmental sustainability with clean technologies, ecological economies and green jobs; digitization, technological innovation, artificial intelligence, robotics and automation; increase in inequality and migratory flows...) major changes are being generated that require innovative actions with a high technological level and with a high demand for environmental sustainability. To act in this global and interconnected society, new technical, professional, personal and social skills and abilities are required, with a marked digital and ecological nature that guarantee sustainable development. The productive and work environment demands professionals with these new skills, characterized by a strong digital and ecological base, and with a determined disposition to keep them updated, participating in continuous and quality training actions throughout life. Obtaining these new skills, through lifelong learning models, will allow the entire population to achieve sustainable employability, in a desirable framework of equality and inclusion. The commitment to joint action with common initiatives will strengthen a global strategy that allows achieving sustainable employability in this context of ecological and digital transformation and transition.